Rome, the site of reverberating memories - Richard Brilliant (Acta ad Archaeologiam et Artium Historiam Pertinentia, 2017)
Great cities with long, continuous histories often preserve on site more than the physical evidence for their reputed distinction, however impressive those remnants may be. Less tangible, but no less significant in establishing their reputation, is the reverberating nature of the histories, myths, and popular stories successively associated with site-engendered memories which shape and reshape the perceptions and responses of residents and citizens alike. Rome is such a place, the Roman Forum, among others, is such a site. The complex interaction between a distinguished remembered past and a self-conscious present variously affects civic responsibility to respect that pasta as well as periodic material and imaginative responses to that obligation.